Dendritic fibrous nano-silica supported gold nanoparticles as an artificial enzyme. Issue 11 (5th March 2018) - Singh, Rustam; Belgamwar, Rajesh; Dhiman, Mahak; Polshettiwar, Vivek
Abstract : We report a dendritic fibrous nano-silica supported gold nanoparticles (DFNS/Au) as peroxidase like artificial enzyme. This study indicates the unique role of fibrous morphology of DFNS for enhancement in enzymatic activity. A solvent dependent selectivity towards a two-electron oxidation product, TMB-diamine, has also been observed. Abstract : Mimicking enzymatic activity is a challenging task. Herein we report dendritic fibrous nano-silica (DFNS) supported gold (Au) nanoparticles (DFNS/Au) as a peroxidase like artificial enzyme. It showed a superior enzymatic activity in 3, 5, 3′, 5′-tetramethylbenzidine (TMB) oxidation chosen as a model reaction, significantly higher than natural horseradish peroxidase (HRP) enzyme as well as other reported nanomaterial based artificial enzymes. A solvent dependent selectivity towards a two-electron oxidation product, TMB-diamine, has also been observed. This study clearly indicates the vital role of the fibrous morphology and unique silica channels of DFNS in the enhancement of the enzymatic activity.